Porphyrin‐Based SOD Mimic MnTnBuOE‐2‐PyP5+ Inhibits Mechanisms of Aortic Valve Remodeling in Human and Murine Models of Aortic Valve Sclerosis - Wanda Anselmo; Emanuela Branchetti; Juan B. Grau; Gen Li; Salma Ayoub; Eric K. Lai; Nancy Rioux; Artak Tovmasyan; Jacqueline H. Fortier; Michael S. Sacks; Ines Batinic‐Haberle; Stanley L. Hazen; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2018)
Background Aortic valve sclerosis (AVSc), the early asymptomatic presentation of calcific aortic valve (AV) disease, affects 25% to 30% of patients aged >65 years. In vitro and ex vivo experiments with antioxidant strategies and antagonists of osteogenic differentiation revealed that AVSc is reversible. In this study, we characterized the underlying changes in the extracellular matrix architecture and valve interstitial cell activation in AVSc and tested in vitro and in vivo the activity of a clinically approved SOD (superoxide dismutase) mimic and redox‐active drug MnTnBuOE‐2‐PyP5+ (BMX‐001). Methods and Results After receiving informed consent, samples from patients with AVSc, AV stenosis, and controls were collected. Uniaxial mechanical stimulation and in vitro studies on human valve interstitial cells were performed. An angiotensin II chronic infusion model was used to impose AV thickening and remodeling. We characterized extracellular matrix structures by small‐angle light scattering, scanning electron microscopy, histology, and mass spectrometry. Diseased human valves showed altered collagen fiber alignment and ultrastructural changes in AVSc, accumulation of oxidized cross‐linking products in AV stenosis, and reversible expression of extracellular matrix regulators ex vivo. We demonstrated that MnTnBuOE‐2‐PyP5+ inhibits human valve interstitial cell activation and extracellular matrix remodeling in a murine model (C57BL/6J) of AVSc by electron microscopy and histology. Conclusions AVSc is associated with architectural remodeling despite marginal effects on the mechanical properties in both human and mice. MnTnBuOE‐2‐PyP5+ controls AV thickening in a murine model of AVSc. Because this compound has been approved recently for clinical use, this work could shift the focus for the treatment of calcific AV disease, moving from AV stenosis to an earlier presentation (AVSc) that could be more responsive to medical therapies.